Leakage current signal parameter of various surface roughness conditions of field-aged polymer insulators - A. Din; M. A. M. Piah; A. R. Abdullah; N. Norddin; F. S. Abdullah (Institute of Advanced Engineering and Science, 2020)
This paper presents the signal parameter of leakage current based on various surface roughness degradation conditions for field-aged high voltage polymer insulators. The arithmetical mean of surface roughness is measured accordingly, and also the surface leakage current signal is captured effectively using data acquisition device via the electrical stress test. With the variation of field-aged insulators ages which include 6-year, 12-year and 18-year, they have been mechanically tested using a surface roughness tester along with electrical testing by using the standard method of inclined plane test. The surface roughness data are recorded meanwhile the leakage current signals are further analyzed using Spectrogram to extract the signal parameter. These include the instantaneous root mean squared current, the instantaneous total harmonic distortion, the instantaneous total non- harmonic distortion and the instantaneous total waveform distortion. From the results of the comparative study, it has shown that the statistical quantity of leakage current signal parameters is responding in an increasing trend with respect to the incremental of the surface roughness. Thus, the signal parameters of the leakage current are able to indicate the degradation conditions of insulator surface.